Multiple Imputation for the Supplementary Homicide Reports: Evaluation in Unique Test Data, 1990-1995, Chicago, Philadelphia, Phoenix and St. Louis - Roberts, John ([Verlag nicht ermittelbar], 2016)
This study was an evaluation of multiple imputation strategies to address missing data using the New Approach to Evaluating Supplementary Homicide Report (SHR) Data Imputation, 1990-1995 (ICPSR 20060) dataset.